Design of badminton training robot with athlete detection - Ordoñez-Avila, J. L.; Pineda, A. D.; Rodriguez, J. D.; Carrasco, A. M. (2022 7th International Conference on Control and Robotics Engineering (ICCRE), 2022)
Robots are used in sports directly, for their participation in some sports competitions, and indirectly, to develop some applications used for training or the recovery of an athlete after intense effort. For robotics in sport, the area where it can be performed is very high, from robots supporting training to robots capable of establishing a 1vs1 game with the athlete. Those that help improve an athlete`s performance, to train, are called launching robots. Those that can establish a continuous game are called player robots. The objective is to develop a badminton training robot that is actioned with an artificial vision. It also seeks to show the great functionality of using microcontrollers in these robots. For this robot`s construction, variables such as the mass of the structure, launch speed, and energy consumption were considered. In this project, there is a quantitative approach with an experimental design that is then analyzed with a V model. In badminton, the coach cannot efficiently analyze the athlete`s performance and movements because he needs to take part in the training, performing the shuttle throws. The badminton robot developed in this paper can perform shuttlecock launches at 4.6 m/s and 2.62 m with a $669 material budget.